Student vehicle registration system with QR code - Vinitha Nair, Mohan (2019)
Safety factor in the university is very important. To make sure the safety of the university and campus areas, UMP Security Department will need a system to record the information of student including their vehicle’s information. Vehicle registration system is developed to ensure the information of all student’s vehicles are registered in the campus. The objective of this project is to design, develop an online student vehicle registration system and produce the official university vehicle’s QR code sticker. This project will focus on managing all student’s vehicle information and generate QR code on the vehicle sticker based on the information that is registered in the system such as student name, student matric number, contact number, session, residence and their vehicle plate number. The problem statement of this project is some students do not register their vehicle and misuse other vehicle’s sticker. The system is expected to help the security staff to detect whether the vehicle is registered or unregistered by scanning the QR code on the sticker and match the information with the owner of vehicle and matric number. This system will be used by UMP students, UMP security management will register the student’s vehicle and print the QR Code sticker. The student vehicle registration is developed using Visual Studio 2017 and Microsoft Access to save student’s information. The methodology used in developing this system is Iteractive Waterfall model. The Iteractive Waterfall model consists of six phases which are planning, analysis, design, implementation and testing. After implementation process, the system is tested by the Head Officer of the Security Management to ensure that all elements in that system is working without any error. It also to ensure that the system has achieve the objectives and can help the Security Guard to block the unregistered vehicles.